Inside Congress I, May 10, 1987 ; Inside Congress II, July 25, 1987 [videorecording]. (GMA Radio Television News and Public Affairs, 1987)
A two-part special report on the history, achievements and failures of the Philippine Congress from 1946-1972, and 1987. Part I deals with the old Congress and the events that led to its abolition during the Martial Law. Part II features significant bills of the old Congress, and performance records of the new Congress under the Aquino administration.